Cibervalleros – A People in Cyberspace? (KULT_online, 2010)
In Daheim in www.cibervalle.com (At home in www.civervalle.com), sociologist Heike Mónika Greschke examines how migration and media communication are related. Using the example of the Paraguayan web forum Cibervalle, she shows how migrants form a virtual global community through day-to-day use of the internet. She concludes that, by using media (mainly the internet), migrants create a new 'homeland' and, thus, substitute their absence at home.Greschke finds that the 'inhabitants' of Cibervalle use the forum not only in order to get to know fellow Paraguayos and maintain contacts in their home country, but also in order to share their everyday life. The author illustrates her analysis with a lively description of Cibervalle’s daily life and successfully links ethnography, migration and media studies.